THE EFFECT OF STUDY FROM HOME (SFH) IMPLEMENTATION AT THE ELEMENTARY LEVEL - Wardani Dwi Wihastyanang; Indra Perdana; Saiful Marhaban (STKIP PGRI Jombang, 2022)
This research was conducted with the aim of obtaining information about the impact of the spread of Covid-19 on the implementation of Study From Home at the elementary level. As well as getting information about the effectiveness of the implementation of Study From Home at the elementary school level. This study uses a qualitative method by studying literature from several sources, both print and electronic media, as well as online books and journals. Journal searches were carried out through Google Scholar with the keywords